A comparative analysis of pre-service teachers' perceptions of self efficacy and emotional intelligence - Gurol, Aysun; Ozercan, Mumine Guher; Yalcin, Hulya (Elsevier Science Bv, 2010)
A consideration of emotion has been traditionally neglected in the context of teaching and teacher education. This has begun to change with the recent research on emotional intelligence (EI). It is highly likely that emotionally intelligent individuals could provide help in how to manage emotions to less emotionally intelligent individuals. This study was reported in this paper was conducted to examine the relationship between pre-service teachers' emotional intelligence (IE) and their self-efficacy. In addition, pre-service teacher differences on EI and self-efficacy beliefs were also examined with in terms of gender. To this end, 248 pre-service teachers were selected from education faculty in Firat University. The participants were asked to complete the Teachers' Sense of Efficacy Scale (Tschannen-Moran and Woolfolk Hoy, 2001) and the Emotional Intelligence Questionnaire (Schutte et al., 1998). The results obtained through using Pearson Product-Moment Correlation showed that there was a positive significant correlation between perceived EI and self-efficacy (r = 0.5). This study provided no support for gender differences in EI and self-efficacy. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Pre-service teacher; self-efficacy; teachers' self-efficacy; emotion; emotional intelligence